2015
DOI: 10.1037/pas0000052
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the Woodcock–Johnson III cognitive tests in a referral sample of elementary school students.

Abstract: The structure of the Woodcock-Johnson Cognitive Battery-Third Edition (WJ Cog) has been extensively explored via confirmatory factor analysis (CFA) with its normative sample, but there has been little research to verify that the same structure holds for students referred for special education services. Likewise, research on the structure of the WJ Cog with exploratory factor analysis (EFA) methods has been rare. Consequently, this study applied both EFA and CFA methods to the scores of 529 elementary school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 71 publications
2
13
1
Order By: Relevance
“…Whereas previous investigations of related ability measures have supported a bifactor structure in which the general factor and the group‐specific factors both have direct effects on observed indicators (e.g., Canivez, ; Canivez, Watkins, & Dombrowski, ; Gignac & Watkins, ; McGill & Dombrowski, ; Strickland, Watkins, & Caterino, ; Watkins & Beaujean, ), the present study indicated that a higher‐order solution is preferred for the KABC‐II Luria model configuration. However, due to model equivalence and the estimation problem encountered (i.e., Heywood case) in specifying the publisher suggested higher‐order model (Figure ) at ages 7–12, it may be argued that the bifactor model should have been given preference because of its advantages (e.g., Reise, ; Rodriguez, Reise, & Haviland, ).…”
Section: Discussioncontrasting
confidence: 88%
“…Whereas previous investigations of related ability measures have supported a bifactor structure in which the general factor and the group‐specific factors both have direct effects on observed indicators (e.g., Canivez, ; Canivez, Watkins, & Dombrowski, ; Gignac & Watkins, ; McGill & Dombrowski, ; Strickland, Watkins, & Caterino, ; Watkins & Beaujean, ), the present study indicated that a higher‐order solution is preferred for the KABC‐II Luria model configuration. However, due to model equivalence and the estimation problem encountered (i.e., Heywood case) in specifying the publisher suggested higher‐order model (Figure ) at ages 7–12, it may be argued that the bifactor model should have been given preference because of its advantages (e.g., Reise, ; Rodriguez, Reise, & Haviland, ).…”
Section: Discussioncontrasting
confidence: 88%
“…Similar results have been observed in studies of the WISC‐IV (Bodin, Pardini, Burns, & Stevens, ; Canivez, ; Gomez, Vance, & Watson, ; Keith, ; Styck & Watkins, ; Watkins, , ) and with other Wechsler scales (Canivez & Watkins, ; Canivez, Watkins, Good, et al ., ; Gignac, , ; Golay & Lecerf, ; McGill & Canivez, , ; Watkins & Beaujean, ; Watkins et al ., ). Nor are these results unique to Wechsler scales as similar findings have been reported with other cognitive scales (Canivez, , ; Canivez, Konold, Collins, & Wilson, ; Canivez & McGill, ; Cucina & Howardson, ; DiStefano & Dombrowski, ; Dombrowski, ; Dombrowski, McGill, & Canivez, ; Dombrowski & Watkins, ; Dombrowski et al ., ; Dombrowski, McGill, et al ., ; Nelson & Canivez, ; Strickland, Watkins, & Caterino, ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been documented in both EFA and CFA studies of the WISC–IV (Bodin et al ., ; Canivez, ; Keith, ; Nakano & Watkins, ; Styck & Watkins, ; Watkins, , ; Watkins et al ., ) and with other versions of Wechsler scales (Canivez & Watkins, ,b; Canivez et al ., , ; Dombrowski et al ., ; Golay & Lecerf, ; Golay et al ., ; Gignac, , ; Lecerf et al ., ; McGill & Canivez, ; Watkins & Beaujean, ; Watkins et al ., ). Further, these results are not unique to Wechsler scales as similar results were also observed with the DAS–II (Canivez & McGill, ), SB5 (Canivez, ), WASI and WRIT (Canivez et al ., ), RIAS (Dombrowski et al ., ; Nelson & Canivez, ; Nelson et al ., ), CAS (Canivez, ), WJ III (Dombrowski, , ,b; Dombrowski & Watkins, ; Strickland, Watkins, & Caterino, ), and the WJ IV Cognitive (Dombrowski et al ., ). The implication of these consistent findings is that primary interpretive weight should be placed on the omnibus FSIQ rather than the first‐order group factor‐based index scores.…”
Section: Discussionmentioning
confidence: 99%